KAJIAN PENERIMAAN DAN PENGGUNAAN BROADBAND MOBILE ACCESS SEBAGAI SARANA LAYANAN INTERNET - AHMAD HUSAIN (LPPM, 2016)
Developments in information technology takes place very quickly. One is the advent of mobile technology Acess. The use of these services has been expanded to all regions in Indonesia, not least Bogor and surrounding areas. One of the study to answer these problems is through the study of information technology adoption process is to identify which factors are affecting the acceptance and use of Broadband Mobile Access and conduct testing to discover the diversity of the interaction of sex, level of education and region of the factors that support Study of Acceptance and Use of Mobile Internet Access For Facility Services Case Study: Regional Bogor. Thus, the model that will be used to assess the acceptance and use of Mobile Acess is through modeling approaches Unified Theory of Acceptance and Use of Technology developed by Venkatesh (2003), which has found four constructs that appear to be significant determinants of direct use Behavior that Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Conditions to explain and predict the acceptance and use of technology by users. And for the collection of data in this study were obtained through questionnaires and subsequently processed data were analyzed using SPSS Statistics and AMOS Graphics. These factors, among others, perceived usefulness, perceived availability, perceived quality, perceived enjoyment, social influence, prices, user attitudes, and intentions to use. Data processing method used is the Structural Equation Model using AMOS software. of processing these data showed that the perception of availability had no effect on user attitudes. While the intention to use is not affected by social influences. Keywords: Unified Theory of Acceptance and Use of Technology, Broadband Mobile Access, Bogor.